THE INFLUENCE OF TEAM WORK ENGAGEMENT ON THE PERFORMANCE OF MEDICAL DEVICE CALIBRATION (Study at Pasuruan Regency Health Center) - supangat, ririn widyowati; Lestari, Endang; Chalidyanto, Djazuly (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Medical equipment that have been suggested in planning for 2021 and have been calibrated at the Primary Health Center in the Pasuruan District Health Office's work area total 10.02% and 21.17% respectively. The goal of this study was to examine how teamwork participation affected the calibration performance outcomes at Pasuruan District Health Center. This kind of study involves 86 informants and analytical observation using a cross-sectional research methodology. The data were examined using a linear regression test.The performance of the medical device calibration team at the Primary Health Center was poor (36.4%), and the findings demonstrated that they were at a teamwork engagement level of commitment. The analysis's findings indicate that the management of writing medical device calibration application letters is significantly impacted by teamwork participation. Additionally, the research of the impact of teamwork engagement on performance outcomes for medical device calibration revealed a substantial impact.Conclusion: There is an influence of team work engagement showing a significant effect on the performance results of medical device calibration. Recommendations for improving the results of medical device calibration performance at the primary health center in Pasuruan Regency were carried out through discussion and research by researchers.